If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 = 5x + -3 Reorder the terms: -3 = -3 + 5x Add '3' to each side of the equation. -3 + 3 = -3 + 3 + 5x Combine like terms: -3 + 3 = 0 0 = -3 + 3 + 5x Combine like terms: -3 + 3 = 0 0 = 0 + 5x 0 = 5x Solving 0 = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 0 + -5x = 5x + -5x Remove the zero: -5x = 5x + -5x Combine like terms: 5x + -5x = 0 -5x = 0 Divide each side by '-5'. x = 0 Simplifying x = 0
| 25-c=97 | | 3/4j+2/5=-23/10 | | 5x+6y=4 | | 1a+2b=5c | | 9/16x^2-1=0 | | r-5=-2 | | 4=-5x-6 | | x-1/13=7/13 | | 9/16x | | 9y-6y-10=21.92 | | 1.2h=-4.8 | | 4y-10=-3 | | 75.25/0.25 | | -2-(3(-2)+7)=11 | | 5z^2-20=0 | | -6m=4 | | a+8=3 | | f(x)=x^4+6x^5+x^4+7x^3+2041 | | -1=7+m | | y/3-6=2 | | y^2+9y+14y=0 | | 8+h=9 | | 8x+17=9x+10 | | (N+15)/6 | | -4+q=-4 | | 8.84/3.4 | | (h+4)(h+3)(h)-126=0 | | 3x^2=-81 | | -4f=30-f | | 8(x+4)-5x= | | F/6-3=4 | | 4-(5x-3)= |